Reserpine induces vascular alpha 2-adrenergic supersensitivity and platelet alpha 2-adrenoceptor up-regulation in dog. - Estan, L. (1990)
1. The aim of the present study was to investigate the influence of catecholamine levels on the regulation of alpha 2-adrenoceptor sensitivity in dogs. 2. Blood pressure and heart rate values at rest, plasma catecholamine levels, platelet and adipocyte alpha 2-adrenoceptors as well as the alpha 2-mediated cardiovascular responses to clonidine (10 micrograms kg-1 i.v., after alpha 1-, beta-adrenoceptor plus muscarinic blockade) or noradrenaline (0.5, 1, 2 and 4 micrograms kg-1 i.v. after alpha 1- and beta-adrenoceptor blockade) were measured before and after reserpine treatment (0.1 mg kg-1 day-1 s.c. over 15 days). 3. Reserpine induced a significant decrease in resting systolic and diastolic blood pressures (213 +/- 2/87 +/- 6 mmHg before vs 158 +/- 5/59 +/- 3 mmHg after treatment) as well as in heart rate (91 +/- 2 beats min-1 before vs 76 +/- 3 beats min-1 after treatment). 4. A 5 min tilt test performed under chloralose anesthesia, failed to modify blood pressure before treatment whereas it induced a significant fall in the same animals after the 15 day treatment. Plasma levels of noradrenaline significantly decreased (262 +/- 58 vs 66 +/- 31 pg ml-1) whereas plasma adrenaline levels were unchanged. 5. The alpha 2-mediated pressor responses to noradrenaline were significantly increased after reserpine. Clonidine induced a marked pressor effect (+72 and +45% in systolic and diastolic blood pressures respectively) after reserpine treatment. This effect was suppressed by administration of RX-821002, a new specific alpha 2-adrenoceptor antagonist.(ABSTRACT TRUNCATED AT 250 WORDS)